Immobilization of Fusarium graminearum β-d-fructofuranosidase using alternative cellulosic supports: Stabilization and production of fructooligosaccharides - Gonçalves, Heloísa Bressan [UNESP] (2015)
The extracellular β-d-fructofuranosidase from Fusarium graminearum was immobilized using hydrophilic cotton, filter paper, multipurpose cloth, sugar cane bagasse, string, or gauze as alternative cellulosic supports, or with cyanogen bromide agarose. All derivatives (support+enzyme) showed high capacity for reuse (up to 23 times). The derivatives obtained with multipurpose cloth and string were stable at 60°C maintaining 80% of their activity for more than 120 min. The filter paper derivative had a halflife (T50) of 27 min at 70°C. When tested for their pH stability (3.0–9.0), all derivatives were more stable than the free enzyme, especially the cotton derivative. The sugarcane bagasse, string, and filter paper derivatives could efficiently produce fructooligosaccharides (FOS) using sucrose as substrate. According to the retention of enzymatic activity, reuse and stabilities, the filter paper and string were the best alternative supports for β-d-fructofuranosidase immobilization, allowing enzyme stabilization and production of FOS.